(untitled) (Baghdad Science Journal, 2011)
This experiment was conducted in order to estimate azulene and apigenin in chamomile flowers. Ethanol extracts were examined singly or in combination with some drugs in their biological activity against some pathogens causing skin infection. Ethanol extract was applied at a concentration of 40 mg/ml for the treatment of induced skin infection of mice. Among the topicals used, Claforan was found the most effective on microorganisms causing skin diseases; ethanol extract was more effective than the drug Candimazole solution 1%. HPLC was used for the determination of azulene and apigenin active compounds of chamomile plant.